Nail Lesions in Dogs and Cats: A Randomized Clinical Study - Salci, Hakan; Dolu, Ceren; Tacar, Kader; Yıldırım, Gül (Acta Scientiae Veterinariae, 2024)
Background: The nail is the horn-like structure of the fingertip. Pathologies in the nail and nail bed of cats and dogs may be primarily related to the nail or may be the clinical symptom of many systemic diseases. Symmetrical or asymmetrical localization of nail lesions may also give clues about the underlying diseases. Although nail pathology in dogs and cats has been previously described, there has not been a randomized clinical study in which nail diseases have been evaluated. Therefore, in this clinical study, it was aimed to randomly determine the nail lesions encountered in dogs and cats brought to our clinics with complaints of another disease and to evaluate the nail lesions encountered. Materials, Methods & Results: The material of the study was formed 26 cats and 35 dogs in different age, gender and breed, which was brought to surgery clinics for different reasons within 1 year and has randomized nail problems. Anamnesis was taken from the patient owners and all the nails of cats and dogs were examined with the help of a magnifying glass in terms of nail integrity, missing or excessive nail formation, nail lesions and pain presence, nail - nail bed and periconnective nail tissue swelling and exudation. All findings were recorded in the “Nail Pathology Follow-up and Evaluation Form”. After nail lesions were divided according to their extremity, the nail lesions of all patients were 1st divided into 2 groups. Asymmetric and symmetrical distribution rates were determined for each nail lesion in groups. Then, with only 1 or more nail lesions in 1 extremity were grouped asymmetrically, and those with 1 or more lesions in multiple extremities were grouped symmetrically. Nail lesions caused by systemic disease were specifically treated and excessive and deformed nails were cut properly by preserving normal nail anatomy. In dogs, 59.56% of the nail lesions were located on the front limbs and 40.44% on the hind limbs, while 41.11% of the nail lesions in cats were located on the front and 58.89% on the hind limbs. In dogs, 62.86% of nail lesions were symmetrical and 37.14% were asymmetrical. In cats, the rates of symmetrical and asymmetrical nail lesions were 38.46% and 61.54%, respectively. In dogs, the nail lesion observed asymmetrically was onychomalacia, while the lesion observed symmetrically is onycholysis. The nail examination findings revealed the most common nail lesion was onychogryposis in 42.85% of the dogs. Onychogryposis was found on the forelimbs in 57.69% and was symmetrical in 60%. In cats, paronychia was the most common nail lesion with a rate of 50%. This lesion was observed asymmetrically in 76.92% of the cases and 56.25% of the cases were located on the front limbs. Discussion: The nails of cats and dogs are biomechanically and histopathologically different from those of humans. Although these terms are not sufficient for the specific diagnosis of the disease, they provide clues about the pathology. In dogs and cats, nails should be trimmed properly and at regular intervals to maintain foot health and help the locomotor system to function normally. Abnormally shaped or deformed nails predispose to gait problems, trauma and the development of some diseases such as pododermatitis. The nails, which are part of the locomotor system, are affected by many local and systemic diseases and nail lesions are often overlooked in clinical practice. In this randomized clinical study, nail lesions encountered in dogs and cats were evaluated comprehensively with their etiologies and clinical descriptions, and the importance of nail diseases in small animal practice was re-emphasized. Keywords: cat, dog, nail lesion.